Integração do Moodle na educação básica: uma prática de avaliação da aprendizagem das equações lineares - Santos, Leticia Arantes Dos (Universidade Federal do Tocantins, 2024)
Assessment should not be related to a simple application of tests; it should be treated in a more structured way and, above all, should not lead the student to frustration. The student should have the opportunity to redo the calculations, with some context that reminds him/her of his/her learning. In this context, we propose an autonomous tool with real-time response, using the Moodle platform, an assessment practice in which the student has the opportunity to make decisions about whether or not to redo the calculations of a wrong answer, with a reminder of the content, all in real time. We used the system of linear equations of two equations with two variables, as a sequence of activities to be assessed. The method used to implement our proposal was to explore the Moodle tools, through trial and error. In this sense, we created a tool, with a flow of activities, involving decisions at each stage of the assessment, which allows the development of the student’s critical capacity and autonomy, contributing to the possibility of application in other situations, as well as making it more comprehensive.